A New Highly Hydrophilic Electrochemical Implant Titanium Surface: A Histological and Biomechanical In Vivo Study. Issue 3 (June 2017) - Trisi, Paolo; Berardini, Marco; Falco, Antonello; Sandrini, Enrico; Vulpiani, Michele Podaliri
Abstract : Purpose: The aim was to compare the osseointegration degree and secondary implant stability between implants with different surface treatments. Materials and Methods: A novel electrochemical treatment was applied to modify the sandblasted and acid-etched surface (SLA) to obtain the new hydrophilic Feeling (FEL) surface presenting a highly soluble and homogenous film made of calcium and phosphorus nanocrystals. Twenty 3.8 × 10-mm dynamix implants (Cortex) were inserted in sheep iliac crests. Sheep were killed after 2 months. Bone-to-implant contact percentage (%BIC) and biomechanical parameters, such as implant stability quotient (ISQ) and value of actual micromotion (VAM), were evaluated for each implants. Results: No implant failures were observed. Implants of test group showed %BIC value 30% higher in respect with control group ( P = 0.001). No statistical differences were detected between the 2 groups in VAM and ISQ values. Conclusion: Both surface treatments were highly osteoconductive because they were able to significantly increase the bone density onto implant surface in respect with that in which they were inserted (D4 bone density). The hydrophilic FEL surface demonstrated an increase of about 216% in BIC in respect with host bone density and an additional 30% more in respect with SLA surface. Faster osseointegration process is desirable in case of early implant loading protocol.